2021
DOI: 10.1002/asi.24473
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a model as an information channel between the physical phenomenon and observer

Abstract: This study proposes a method to assess the accuracy limit of the measurements of physical variables to formulate a model, from the perspective of storing, transmitting, processing, and using of information by an observer. The results show the existence of a problem that advanced statistical methods are provably incapable of solving due to the presence of initial and inevitable model uncertainties arising from a qualitative set of base quantities and the number of variables which are considered, even before ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 43 publications
(68 reference statements)
0
22
0
Order By: Relevance
“…Below, we consider the physical perspective of the modelling process. For the purposes of this article, a model is a communication channel between the object under study and the researcher using a system of units to select variables [2]. Here it is appropriate to make one important remark.…”
Section: Beginnings Of the Informational Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Below, we consider the physical perspective of the modelling process. For the purposes of this article, a model is a communication channel between the object under study and the researcher using a system of units to select variables [2]. Here it is appropriate to make one important remark.…”
Section: Beginnings Of the Informational Approachmentioning
confidence: 99%
“…This channel has some properties that depend on the thinker's will. The axiomatic structure of the communication channel when modelling a physical object includes the following statements [2]: Age 1. The variables in the model are selected by the thinker from a system of units, such as Anglo-American units, Planck units, or centimetre-gram-second (CGS).…”
Section: Beginnings Of the Informational Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] [5] [6], some researchers recognize that it is possible to consider the model as an information channel between the observed object and the researcher ref. [7].…”
Section: Initial Backgroundmentioning
confidence: 99%
“…Given that μ SI is a constant, each FIQ has a limited amount of information ref. [7] and the number of FIQs in the model is always limited; it can be concluded that the number the information contained in the SI and in the model is limited.…”
Section: Initial Backgroundmentioning
confidence: 99%